Search for displaced supersymmetry in events with an electron and a muon with large impact parameters - Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Friedl, M; Frühwirth, R; Ghete, V M; Hartl, C; Hörmann, N; et al. (Physical review letters, 2015)
A search for new long-lived particles decaying to leptons is presented using proton-proton collisions produced by the LHC at √[s]=8 TeV. Data used for the analysis were collected by the CMS detector and correspond to an integrated luminosity of 19.7 fb(-1). Events are selected with an electron and muon with opposite charges that both have transverse impact parameter values between 0.02 and 2 cm. The search has been designed to be sensitive to a wide range of models with nonprompt e-μ final states. Limits are set on the "displaced supersymmetry" model, with pair production of top squarks decaying into an e-μ final state via R-parity-violating interactions. The results are the most restrictive to date on this model, with the most stringent limit being obtained for a top squark lifetime corresponding to cτ=2 cm, excluding masses below 790 GeV at 95% confidence level.